ANALISIS PENGEMBANGAN SISTEM E-BUSINESS UNTUK UMKN PENGGILINGAN PADI DI DUSUN X KECAMATAN BATANG KUIS KABUPATEN DELI SERDANG - Aulia Azmi Lubis; Muhammad Farhan Harahap; Nurbaiti Nurbaiti (Fakultas Ekonomi dan Bisnis Universita Labuhanbatu Sumatera Utara Indonesia, 2021)
Indonesian is an agrarian country where the most of the population makes a living form agriculture, one of which is : growing rice. It is polished in the process of growing rice. Along with development of the times, the rice milling method provides maximum result in a relatively short time. You need to update the time. This business system is the production, distribution or sale of goods. Other obstacles continue to emerge, both through record keeping and manual trading. Confirm to learn the benefits of milling services. This study focuses on the evolution of e-business. It is a transaction management system for rice business, improve customer, service, shredding, selling, shopping and othe electronic transaction data management. The research phase includes: User requirements, data collection, analysis of functional and non-functional requirements for the system, system desing, development and testing.